Demographic development of Qassim region – An analytical study of population variables in the period 2010 – 2019 - Abbakar, Mustafa Mohamed Ali (Journal of Humanities & Social Sciences, 2022)
Population variables are among the most important indicators that reveal the conditions of the population in any country in the world, and the evolution of these variables is evidence of the status of any place in terms of population strength, influence and weakness in economic, cultural, social and other aspects, whether for the whole country or Part of it as a local region. In framework of that, this study comes to explore the demographic development of the Saudi Qassim region during a decade, from 2010 AD to 2019, and the study aimed to highlight the relationship between demographic influences in Qassim and the whole Saudi country, as well as analyzing these indicators and clarifying how they develop. The study used the regional approach, as well as the analytical statistical method to highlight and analyze the population digital data.The study concluded that Qassim region is linked to the effects of the general population conditions in the Saudi state in all demographic indicators, and that the overall picture of the Qassim population is a representative sample of all residents of the Saudi state.
Keywords: Demographic development; Qassim region; Population variables; Population growth